Unpacking the Impact of the Merdeka Mengajar Platform on Teacher Performance: A CIPP Model Evaluation - Musafir, Musafir; Sukirman, Sukirman; Ilham, Dodi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study evaluates the implementation of the Platform Merdeka Mengajar (PMM) and its impact on improving teacher performance through the Context, Input, Process, and Product (CIPP) evaluation model. As a flagship initiative of Indonesia’s Ministry of Education, PMM provides self-paced training modules, instructional resources, assessment tools, and digital portfolios to support teachers in delivering the Merdeka Curriculum. Employing a qualitative approach, data were collected through semi-structured interviews, classroom observations, and document analysis involving eight teachers and one principal at a junior secondary school in Indonesia. The findings indicate that PMM is contextually aligned with the evolving needs of educators, particularly in promoting independent learning and responsive teaching. While infrastructure and resources were generally adequate, limited digital fluency and time constraints hindered optimal use. Teachers are actively engaged with the platform, supported by institutional mechanisms like Komunitas Belajar, for collaborative reflection. The evaluation showed improved pedagogical competence, classroom management, and student engagement. Despite some obstacles, PMM demonstrates strong potential as a digital innovation for professional development. This study recommends sustained policy support, user-centered platform improvements, ongoing training, and a robust monitoring and evaluation framework to enhance its effectiveness. The results provide valuable insights for policymakers and school leaders seeking to integrate technology into teacher development systems.